Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/00365521.2015.1056223
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon enteroscopy-assisted endoscopic retrograde cholangiography for Roux-en-Y reconstruction patients with papilla of Vater or bilioenteric anastomosis

Abstract: DBE-ERC was effective for both populations with biliary disorders. Reaching the blind end was more difficult but ERC was easier for patients with BEA in terms of procedure time rather than success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…Furthermore, Tsou et al . suggested the efficacy and safety of large balloon dilation for patients with not only the intact papilla of Vater but also a bilioenteric anastomotic stricture . Our statistical analysis showed that balloon diameter was not associated with CJS recurrence, whereas remaining waist was significantly associated with CJS recurrence in the patients who underwent balloon dilation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, Tsou et al . suggested the efficacy and safety of large balloon dilation for patients with not only the intact papilla of Vater but also a bilioenteric anastomotic stricture . Our statistical analysis showed that balloon diameter was not associated with CJS recurrence, whereas remaining waist was significantly associated with CJS recurrence in the patients who underwent balloon dilation.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, the development of balloon‐assisted enteroscopy (BAE) has enabled endoscopists to accomplish endoscopic retrograde cholangiopancreatography (ERCP) and several procedures associated with BAE‐ERCP for CJS and PJS, such as balloon dilation and/or stent deployment, with high success rates . However, these results were limited to only short‐term outcomes, and there have been few reports regarding long‐term results after BAE treatment . Additionally, the appropriate BAE‐ERCP procedures for CJS and PJS remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pancreaticobiliary diseases and altered anatomy were previously managed either by laparoscopy‐assisted ERCP, percutaneously or by double balloon‐assisted ERCP. Although the technical success rate for the double balloon‐assisted approach is greater than 80% in expert hands, the procedure is technically cumbersome and time‐consuming . Recently, under EUS‐guidance, LAMS have been successfully placed between the gastric remnant and the excluded stomach (Video S3).…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…Although the technical success rate for the double balloon-assisted approach is greater than 80% in expert hands, the procedure is technically cumbersome and timeconsuming. 24 Recently, under EUS-guidance, LAMS have been successfully placed between the gastric remnant and the excluded stomach (Video S3). Usually the LAMS are left in situ for 2-3 weeks for the transmural tract to mature.…”
Section: Gastric Outlet Obstructionmentioning
confidence: 99%